Evaluating iron deficiency anaemia in the third trimester of pregnancy with haematological parameters and serum ferritin concentration - Muthukumaran, Niranjani Selva; Thangappah, Radha B. P.; Azad, Amrin; Sravaniy, Kesari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Iron deficiency is the commonest cause of anaemia and at least half of anaemia cases will have causes other than iron deficiency. The objective of this study was to determine the prevalence of iron deficiency anaemia among antenatal mothers based on haematological parameters and serum ferritin levels. Methods: This was a hospital based cross sectional study, conducted at Meenakshi Medical College and Research Institute, Kancheepuram from January 2017 to June 2018. Two hundred antenatal mothers who were diagnosed with anaemia in the third trimester of pregnancy were evaluated by haematological parameters and serum ferritin assay. Results: 38% of women had mild anaemia, 50% had moderate anaemia and 12% had severe anaemia. On peripheral smear, 60% had microcytic hypochromic anaemia indicating iron deficiency, and 12% had megaloblastic anaemia. In 41% of cases, the mean corpuscular volume was <82fL indicative of iron deficiency. Among the 120 women diagnosed with iron deficiency anaemia on smear, the mean ferritin level was 16.62±73.42 (less than 30µg/l). There was a statistically significant low levels of serum ferritin levels in those diagnosed with iron deficiency anaemia (P < 0.05). The serum ferritin level was >160µg/lit in 19% of cases. Conclusions: Based on the haematological parameters and serum ferritin estimation, in 60% of cases, anaemia was due to iron deficiency. Before initiating treatment, it is important to differentiate various types of anaemia, so that appropriate treatment can be given.